2022
DOI: 10.20944/preprints202201.0342.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Anthocyanin-Rich Vegetables for Human Consumption – Focus on Potato, Sweetpotato and Tomato

Abstract: Malnutrition, unhealthy diets, and lifestyle changes have become major risk factors for non-communicable diseases while ad-versely impacting economic growth and sustainable development. Anthocyanins, a group of flavonoids that are rich in fruits and vegetables, contribute positively to human health. This review focuses on genetic variation harnessed through crossbreeding and biotechnology-led approaches for developing anthocyanins-rich fruit and vegetable crops. Significant progress has been made in identifyin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 91 publications
0
4
0
Order By: Relevance
“…The descriptive statistics of the values including the means and standard deviation (SD) values for each subgroup of surface roughness showed that control group had the higher mean value in surface roughness (1.4620) and the lowest mean value was found in group containing 3%ZrO2 (0.0466) as shown in Tables (2) and Figure (3)…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The descriptive statistics of the values including the means and standard deviation (SD) values for each subgroup of surface roughness showed that control group had the higher mean value in surface roughness (1.4620) and the lowest mean value was found in group containing 3%ZrO2 (0.0466) as shown in Tables (2) and Figure (3)…”
Section: Resultsmentioning
confidence: 99%
“…Waste CAM / CAD Effect Of The 198 study population was completely clueless regarding knowledge pertaining to the recycling process. They were unaware of the proper disposal of some nondegradable dental materials (3,4,5,6). Acrylic resin polymethyl methacrylate (PMMA) has been the most popular material for the construction of dentures for many decades as it has many advantages such as stability, good aesthetics, accurate fit, in the oral environment, inexpensive equipment's, easy clinical and laboratory manipulation (7, 8, 9).…”
Section: Introductionmentioning
confidence: 99%
“…The biological activities of polyphenols in potatoes might be helpful for breeders in designing new varieties with numerous health benefits, for both pharmaceutical and nutraceutical industries (Rasheed et al, 2022). The inclusion of anthocyanins as a characteristic target in breeding programs can ensure the development of cultivars to satisfy the nutritional requirements in human consumption in the developing world (Mattoo et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…A dietary regime enriched in polyphenols, tomato NILs in the genetic background of Bronze-tomato enriched in flavonols, anthocyanins, and stilbenoids (Scarano et al, 2018), administered to Winnie and control mice showed significant induction of anti-inflammatory genes and may efficiently support IBD remission affecting the intestinal dysbiosis (Liso et al, 2018). Both crossbreeding and biotechnology approaches were used to develop anthocyanins rich germplasm/cultivars (Mattoo et al, 2021), which may be further crossed to develop NILs differing in a particular biochemical compound to investigate its long-term effect on human health. The transcription factors involved in regulating the structural and other genes in the biosynthetic pathway of anthocyanin are depicted in…”
Section: Model Food To Assess Diet-health Complexitymentioning
confidence: 99%